Nosocomial Infection in Burn Unit of Cipto Mangunkusumo Hospital, Jakarta - Mahandaru, Danu; Wardhana, Aditya (Lingkar Studi Bedah Plastik Foundation, 2012)
Backgrounds: Burn patients, due to the immune compromise effects of their injury have a high risk for infections. The major cause of infection is the hospital environment contamination. This study was conducted to detect and identify isolated bacteria from patients and hospital environment in the Burn Unit and determine their antibiotics pattern in response to commonly used antimicrobial agents; in order to give recommendations for management of bacterial infections and drug-resistance. Patients and Methods: Retrospective observational study was conducted reviewing the database of Burn Unit in RSCM from January until December 2010. The characteristics of microorganisms found on the burn wound were compared to those obtained from the environments such as from the air, bathing water, and medical instruments. The pattern of microorganisms and their sensitivity-resistance characteristics were noted.Result: The pattern shows that nosocomial infection in the Burn Unit of RSCM was high. Klebsiella pneumoniae found on the burn wound eschars mimics those obtained from the air within the Burn Unit. Strains of MRSA were also found on screening.Conclusion: Our findings emphasize the need for careful disinfection and more strict infection control procedures in areas that serve immune suppression individual, such as burn patients.